The Importance of Social Media in Increasing Brand Reputation and Consumer Satisfaction in a Digital Context - Nabila Almanova; Bhetrix Ayu Varadigya; Diva Native Deen; Anugerah Akbar Prasetyo; Davin Ridho Pratama; Dwi Puspa Arum (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines how social media improves brand reputation and consumer satisfaction in the digital internet era. With the increasing use of social media as a marketing tool, businesses must understand how consumer interactions with brands can influence consumer perceptions and customer satisfaction levels. A good brand reputation can strengthen consumer loyalty, increase trust in products or services, and influence purchasing decisions. Consumer satisfaction not only depends on product quality, but also on how the company manages interactions and provides services via social media. This research aims to explore how social media can influence brand reputation and consumer satisfaction in the current digital business context. It is hoped that the findings from this research can provide useful insights for entrepreneurs in utilizing social media more effectively to build a positive reputation and increase overall consumer satisfaction.